The performativity of sustainability: Assessing the continuity of artisanal fishing livelihoods in Galápagos' precarious waters - Burke, Adam (Social Anthropology, 2017)
This work is about how people develop strategies to make sense of and to deal with the challenges of situating themselves within the global push for 'sustainability.' Sustainability is a concept that I understand to be imagined, socially constructed, remade and ritualized as global actors tote the 'sustainable development' discourse globally and impose it upon local actors' practices. Such foisting typically promises to resolve socio-ecological problems by providing communities with certainties and stabilities such as redeeming issues linked to threatened eco-systems and local actors' precarious livelihoods therein. However, I argue that 'sustainability' indeed fails to fulfil its ideological aspirations. In this light, I take the stance that sustainability is performative, and therefore, enacted through sets of relationships which require critical interrogation. I use the example of artisanal fishermen in the Galápagos Islands to demonstrate how: (i) they deal with local managing authorities and the enterprise of sustainability that disturb their daily lives on land and at sea; (ii) they situate themselves within co-management processes; and (iii) their performativities allow them to make sense of and to deal with their precarious livelihoods by remaking, challenging, and subverting 'sustainability' in effort to remain relevant in Galápagos' evolving eco-political landscape. This occurs, I argue, as fishermen enact performativities that are situated in their material practices, collective, and authoritative. Notions of performativity thus contribute to conceptual understandings of how global actors' ambitions to remake local actors' practices 'sustainably' produces and distributes precarity – and therefore exposes how the latter deal with the precarity resulting from their attempts to remain relevant in Galápagos' eco-political landscape over time.